СВЯЗАННАЯ ЗАДАЧА ТЕРМОУПРУГОСТИ В ДЕФОРМАЦИЯХ ДЛЯ ИЗОТРОПНОГО ПАРАЛЛЕЛЕПИПЕДА - Джумаёзов, У.З. (SCIENCE and SOCIETY, 2024)
This work is devoted to mathematical and numerical modeling of the coupled dynamic problem of thermoelasticity in deformations. A numerically related boundary value problem of thermoelasticity is formulated and solved in deformations for a parallelepiped with the corresponding initial and boundary conditions